New Orthalicidae (Mollusca, Gastropoda) from Venezuelan Guayana: unravelling secrets from the Lost World - Breure, Abraham S.h. (Zootaxa, 2009)
Land snails of the family Orthalicidae from Venezuelan Guayana are revised and the following new species are described: Drymaeus (D.) rex, Plekocheilus (Eurytus) huberi, P. (E.) nebulosus, P. (E.) sophiae, and P. (E.) tepuiensis. Drymaeus (D.) griffini Haas, 1955 is now placed in the synonymy of D. (D.) extraneus (Haas, 1955). In addition, the genitalia of Plekocheilus (Eurytus) tatei Haas, 1955 are described for the first time. Plekocheilus (Eudolichotis) gibber (Oberwimmer, 1931) is now considered a member of P. (Eurytus). As a consequence, Antitragus Oberwimmer, 1931 is now regarded a junior synonym of Eurytus Albers, 1850. Of the 16 taxa treated here, 14 are endemic to the table-top mountains (‘tepuis’) of this area. A Principal Component Analysis has been used to study the biotic and abiotic factors that may influence species diversity and distributions. Habitat diversity explained 65% of the variability and was mainly influenced by plant diversity, number of forest types, elevation and slope area of the tepuis.